Neural cryptography - Protić, Danijela D. (Vojnotehnički glasnik / Military Technical Courier, 2015)
Neural cryptography based on the tree parity machine (TPM) is presented in this paper. A mutual learning-based synchronization of two networks is studied. The training of the TPM based on the Hebbian, anti-Hebbian and random walk as well as on the secure key generation protocol is described. The most important attacks on the key generation process are shown.
Keywords: Tree parity machine; Neural networks; Cryptography